Can Nimesulide Nanoparticles Be a Therapeutic Strategy for the Inhibition of the KRAS/PTEN Signaling Pathway in Pancreatic Cancer? - Ferreira, Roseane Guimarães; Narvaez, Luis Eduardo Mosquera; Espíndola, Kaio Murilo Monteiro; Rosario, Amanda Caroline R. S.; Lima, Wenddy Graziela N.; Monteiro, Marta Chagas (Frontiers in Oncology, 2021)
Pancreatic cancer is an aggressive, devastating disease due to its invasiveness, rapid progression and resistance to surgical, pharmacological, chemotherapy, and radiotherapy treatments. The disease develops from PanINs lesions that progress through different stages. KRAS mutations are frequently observed in these lesions, accompanied by inactivation of PTEN, hyperactivation of the PI3K / AKT pathway, and chronic inflammation with overexpression of COX-2. Nimesulide is a selective COX-2 inhibitor that has shown anticancer effects in neoplastic pancreatic cells. This drug works by increasing the levels of PTEN expression and inhibiting proliferation and apoptosis. However, there is a need to improve Nimesulide through its encapsulation by solid lipid nanoparticles to overcome problems related to the hepatotoxicity and bioavailability of the drug.